Profil de la polyarthrite rhumatoïde en consultation rhumatologique à Lomé (Togo) - K., Kakpovi; V., Koffi-Tessio; P., Houzou; E., Fianyo; M., Kolou; M.I, Kuéviakoé; E., Padaro; K., Tagbor; O., Oniankitan; M., Mijiyawa (European Scientific Journal, ESJ, 2017)
Objective: To determine epidemiological, clinical, therapeutic aspects and outcomes of rheumatoid arthritis (RA) in rheumatologic consultation at lome (Togo). Patients and method: This was retrospective study carried out from 1 stJanuary 1990 to 31 stDecember 2015 in the rheumatology department. The study included all patients suffered from RA in rheumatologic consultations and who fulfilled the 2010 ACR and EULAR’s criteria. Results: Ninety two (77 women and 15 men) out of 25.992 patients (0.3%) examined in 25 years had suffered from RA. The mean age at admission was 42 years (range: 17-82 years). The median duration of the diseases was four years (range: 14days – 20 days). The diseases onset was polyarticular with 86% of the patients and oligoarticular with the thirteen others (14%). The proximal interphalangeal (PIP) joints and metacarpophalangeal (MCP) joints are involved in 81,5 % of cases; and the wrists in 77,2% of cases. The rheumatoid hip was observed in four patients. Forty-two of the patients (45,6%) presented RA deformities. Bilateral MCP and IPP joint early erosion was observed in 36 patients (39,1%) and bilateral carpal diffuse osteoporosis in 44 patients (47,8%). The ankylosis of the carpal bones was observed in 26 patients (28,2 %). Rheumatoid factor was positive in 44% of patients. Methotrexate was the most commonly disease-modifying antirheumatic drugs used in 44,4% of the patients. The disease was improved in 89% of patients. Conclusion: Rheumatoid arthritis seems relatively rare in Togo. It’s diagnosis is often made at the established phase and methotrexate remains the cornerstone of the treatment.